An Organic Approach to Customer Engagement and Loyalty. Issue 4 (3rd July 2020) - Prentice, Catherine; Wang, Xuequn; Lin, Xiaolin
ABSTRACT: The paper draws on customer engagement literature to propose an organic approach to achieving customer loyalty. The organic approach is reflected in customers' volitional engagement in an online brand community without any deliberate marketing endeavors and incentives from the brand organization. This research employs a longitudinal study focusing on consumers in the United States of America (USA) and examines the relationships between organic customer-engagement behaviors and customer loyalty. Based on expectancy theory, customer perceived benefits are proposed to intervene in these relationships. Results from the longitudinal investigation support the study propositions. Discussion and implications are provided for researchers and practitioners.